Natural history of the narrow endemics Ipomoea cavalcantei and I. marabaensis from Amazon Canga savannahs - Babiychuk, Elena; Kushnir, Sergei; Vasconcelos, Santelmo; Dias, Mariana Costa; Carvalho-Filho, Nelson; Nunes, Gisele Lopes; dos Santos, Jorge Filipe; Tyski, Lourival; da Silva, Delmo Fonseca; Castilho, Alexandre; Fonseca, Vera Lucia Imperatriz; Oliveira, Guilherme (Scientific reports, 2017)
Amazon comprises a vast variety of ecosystems, including savannah-like Canga barrens that evolved on iron-lateritic rock plateaus of the Carajás Mountain range. Individual Cangas are enclosed by the rain forest, indicating insular isolation that enables speciation and plant community differentiation. To establish a framework for the research on natural history and conservation management of endemic Canga species, seven chloroplast DNA loci and an ITS2 nuclear DNA locus were used to study natural molecular variation of the red flowered Ipomoea cavalcantei and the lilac flowered I . marabaensis . Partitioning of the nuclear and chloroplast gene alleles strongly suggested that the species share the most recent common ancestor, pointing a new independent event of the red flower origin in the genus. Chloroplast gene allele analysis showed strong genetic differentiation between Canga populations, implying a limited role of seed dispersal in exchange of individuals between Cangas. Closed haplotype network topology indicated a requirement for the paternal inheritance in generation of cytoplasmic genetic variation. Tenfold higher nucleotide diversity in the nuclear ITS2 sequences distinguished I . cavalcantei from I . marabaensis , implying a different pace of evolutionary changes. Thus, Canga ecosystems offer powerful venues for the study of speciation, multitrait adaptation and the origins of genetic variation.